Writing Indian, Native conversations - Purdy, John Lloyd (Book collections on Project MUSE., 2009)
By revisiting some of the classics of the genre and offering critical readings of their distinctive qualities and shades of meaning, Purdy celebrates their dynamic literary qualities. Interwoven with this personal reflection on the last thirty years of work in the genre are interviews with prominent Native American scholars and writers (including Paula Gunn Allen, Simon Ortiz, Gerald Vizenor, Sherman Alexie, and Louis Owens), who offer their own insights about Native literatures and the future of the genre. In this book their voices provide the original, central conversation that leads to read.